2007
DOI: 10.1111/j.1365-2966.2007.11457.x
|View full text |Cite
|
Sign up to set email alerts
|

The connection between metallicity and metal-line kinematics in (sub-)damped Lyα systems

Abstract: A correlation between the metallicity, [M/H], and rest-frame Mg II equivalent width, W λ2796 r

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 76 publications
(114 reference statements)
2
74
1
Order By: Relevance
“…Note that the interpretation of broad high-ion components in DLAs and sub-DLAs as hot and collisionally ionized is different from the interpretation of the O vi components in the IGM at z > ∼ 2, which (generally) appear to be photoionized (Carswell et al 2002;Bergeron et al 2002;Levshakov et al 2003;Bergeron & Herbert-Fort 2005;Reimers et al 2006;Lopez et al 2007), though see Reimers et al (2001) and Simcoe et al (2002Simcoe et al ( , 2006. Ledoux et al (2006) have presented a [Z/H]-∆v Neut correlation in DLAs and sub-DLAs, and have interpreted it as implying an underlying mass-metallicity relation (see also Wolfe & Prochaska 1998;Ledoux et al 1998;Murphy et al 2007;Prochaska et al 2007a). In this interpretation, ∆v Neut traces motions due to gravity.…”
Section: Narrow and Broad Componentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Note that the interpretation of broad high-ion components in DLAs and sub-DLAs as hot and collisionally ionized is different from the interpretation of the O vi components in the IGM at z > ∼ 2, which (generally) appear to be photoionized (Carswell et al 2002;Bergeron et al 2002;Levshakov et al 2003;Bergeron & Herbert-Fort 2005;Reimers et al 2006;Lopez et al 2007), though see Reimers et al (2001) and Simcoe et al (2002Simcoe et al ( , 2006. Ledoux et al (2006) have presented a [Z/H]-∆v Neut correlation in DLAs and sub-DLAs, and have interpreted it as implying an underlying mass-metallicity relation (see also Wolfe & Prochaska 1998;Ledoux et al 1998;Murphy et al 2007;Prochaska et al 2007a). In this interpretation, ∆v Neut traces motions due to gravity.…”
Section: Narrow and Broad Componentsmentioning
confidence: 97%
“…We are partly motivated by the recent work of Ledoux et al (2006), who reported a correlation between low-ion line width ∆v Neut and metallicity [Z/H] in a sample of 70 DLAs and sub-DLAs, covering over two orders of magnitude in metallicity (see also Wolfe & Prochaska 1998;Murphy et al 2007;Prochaska et al 2007a). Since the line widths of the neutral species are thought to be gravitationally-dominated, the broader lines may be tracing the more massive halos, and so the ∆v Neut -[Z/H] correlation has been interpreted as evidence for an underlying massmetallicity relation.…”
Section: Introductionmentioning
confidence: 99%
“…While some authors present observations that suggest strong Mg ii absorbers originate primarily in galactic superwinds from low-mass galaxies (Prochter et al 2006;Bouché et al 2006;Murphy et al 2007), others show that Mg ii absorbing galaxies resemble typical field galaxies ( Zibetti et al 2005;Kacprzak et al 2007;Nestor et al 2007) and the covering fraction of Mg + ions is roughly 50% (Tripp & Bowen 2005). A particularly puzzling result is the anticorrelation between W r (2796) ( hereafter W r ) and the clustering amplitude by Bouché et al (2006, hereafter B06).…”
Section: à2mentioning
confidence: 99%
“…The probability of resolving these features can be increased by finding gas clouds with simple kinematics, which are more common at the lowest metallicity (Ledoux et al 2006;Murphy et al 2007;Prochaska et al 2008;Jorgenson et al 2013;Neeleman et al 2013;Cooke et al 2015); in general, the most metal-poor systems exhibit simple and quiescent kinematics. Given the low metallicity of the DLA toward J1358+0349, based on the ESI spectra, we acquired two high-quality, highresolution spectra of this quasar with the aim of measuring D/H.…”
Section: Observations and Data Reductionmentioning
confidence: 99%